Gas fees on the Ethereum blockchain: from foundations to derivative valuations - Meister, Bernhard K.; Price, Henry C. W. (Frontiers in Blockchain, 2024)
The 'gas fee', paid for inclusion in the blockchain, is analyzed in two parts. First, we consider how 'effort' in terms of resources required to process and store a transaction turns into a 'gas limit', which, through a fee, comprised of the 'base' and 'priority fee' in the current version of Ethereum, is converted into the cost paid by the user. We adhere closely to the Ethereum protocol to simplify the analysis and to constrain the design choices when considering 'multidimensional gas'.Second, we assume that the 'gas' price is given 'deus ex machina' by a fractional Ornstein-Uhlenbeck process and evaluate various derivatives. These contracts can, for example, mitigate gas cost volatility. The ability to price and trade 'forwards' besides the existing 'spot' inclusion into the blockchain could enable users to hedge against future cost fluctuations.Overall, this paper offers a comprehensive analysis of gas fee dynamics on the Ethereum blockchain, integrating supply-side constraints with demand-side modelling to enhance the predictability and stability of transaction costs.